Obstetric implications of maternal chronic hepatitis B virus infection - Terence T. Lao (Open Exploration Publishing Inc., 2021)
Antenatal screening for hepatitis B surface antigen seropositivity is widely adopted to identify pregnant women with chronic hepatitis B virus (HBV) infection in order to target their newborn infants for combined passive-active neonatal immunization to prevent the maternal-to-child transmission of HBV. It is less certain whether the presence of chronic HBV infection in these largely asymptomatic women could impact their pregnancy outcome. There is now gathering information in the literature, though sometimes conflicting, on the obstetric implications of chronic HBV infection. The conflicting data is most probably related to confounding factors such as the immunological phase of chronic HBV infection, viral genotype and activity, presence of hepatic inflammation and other co-existing liver disorders such as non-alcoholic fatty liver disease, and coinfection with other virus such as hepatitis C virus and micro-organisms, which are usually not examined, but which could have made significant influence on the occurrence of many of the pregnancy complications and adverse fetal and neonatal outcome. For pregnancy complications, the evidence suggests association with increased gestational diabetes mellitus, preterm birth, intrahepatic cholestasis of pregnancy, caesarean delivery, and postpartum haemorrhage, probably increased placental abruption and prelabour rupture of the membranes, and no effect or a reduction in the hypertensive disorders of pregnancy, especially preeclampsia. For perinatal outcome, there may be increased miscarriage and fetal malformations, and increase in both low birthweight and large-for-gestational age/macrosomic infants, as well as increased intrauterine fetal demise/stillbirth and fetal distress. However, most studies have not elaborated on the mechanisms or explanations of many of the adverse outcomes. Taken together, maternal chronic HBV infection increases the risk of adverse obstetric outcome overall, but further prospective studies are warranted to elucidate the reasons and mechanisms of, and with a view to mitigating, these adverse obstetric outcomes.